Citrus Leprosis Fruit, Leaf, and Stem Symptom Identification - Amit Levy; Ozgur Batuman; Megan M. Dewdney; Jamie D. Burrow (EDIS)
This new two-page handout provides a brief summary of citrus leprosis symptoms. Written by Amit Levy, Ozgur Batuman, Megan M. Dewdney, and Jamie D. Burrow and published by the UF/IFAS Plant Pathology Department.